EFFECTIVENESS VALUE OF THE USE OF SNAKES AND LADDERS LEARNING MEDIA ON STUDENT LEARNING OUTCOMES - Maulana, Akbar; Fitri Silvia Sofyan; Tridays Repelita (Journal Civics And Social Studies, 2024)
The study's objective was to determine the value of the effectiveness of the use of snakes and ladders learning media on the learning outcomes of class VIII students at SMP IT Al-Ikhwan Karawang. This research uses a survey method. The purposive sampling methodology was utilized in the research, which employed a Non-probability sampling method. The sample used was 40 students from a total population of 100 students. The SPSS 27 application assisted in conducting the data analysis, consisting of validity and reliability tests, prerequisite analysis tests. In accordance with the outcomes of the research, the hypothesis test shows that there is an effectiveness of 67.2% between the use of snakes and ladders learning media on the learning outcomes of class VIII students at Al-Ikhwan Karawang IT Junior High School.